Implementation of the Merdeka Curriculum in Arabic Language Subjects at Alif Laam Mim Islamic Yunior High School Surabaya - Munawaroh, Wardatul; Rofiq, Isadur (Journal of Arabic Language Studies and Teaching, 2024)
This article examines the implementation of the independent curriculum in Arabic subjects at Alif Laam Mim Islamic Yunior High School Surabaya. This curriculum change requires educational units to adhere to the concepts of the curriculum that have been implemented. This study used a descriptive qualitative method. Data collection was carried out through interviews and observations. The data analyzed were obtained from interviews with research subjects, namely Arabic language education teachers who teach in the seventh and eighth grades at MTs Alif Laam Mim Surabaya. This research shows that Alif Laam Mim Islamic Yunior High School has implemented the independent curriculum concept at the seventh and eighth-grade levels. In teaching and learning, teachers apply differentiated instruction that prioritizes students' abilities, talents, and interests. Teachers also focus on character development in each lesson. However, the concept of the independent curriculum still needs to be fully understood by all teachers, so they must learn to grasp the concept fully continuously.